HIGH LEVEL OF miR-454 EXPRESSION IN SERUM/PLASMA OF UVEAL MALIGN MELANOM PATIENTS - Masoumeh Hassani; Demet Akdeniz Ödemiş; Tunay Doğan; Samuray Tuncer; Hülya Yazıcı (Sabiad)
Objective: Uveal malignant melanoma (UMM) is a cancer type that has a poor prognosis and high metastasis tendency and is difficult to diagnose early. Therefore, non-invasive diagnostic and prognostic markers are needed in this disease. In the study, it was investigated the expression level of miR-454 in serum /plasma samples of UMM patients and also evaluated the feature of a diagnostic and prognostic biomarker of miR-454. Material and Method: This study was performed on peripheral blood samples from 72 patients with UMM and 72 healthy controls matched for age, sex, and ethnicity, who applied to Istanbul University, Istanbul Faculty of Medicine, Department of Ophthalmology and Oncology Institute. MicroRNA-454 expression level in cell-free RNA (cfRNA) isolated from serum/plasma was investigated by the Real-Time PCR (RT-PCR). The expression level of miR-454 determined according to the reference gene was evaluated by comparing it with patients and healthy controls. Results: It was found that the expression level of miR-454 increased 4.14 times in the patient group compared to the healthy controls, and it was statistically significant. In the study, it was shown that there is a significant relationship between miR-454 expression level and smoking and alcohol intake. When the mRNAs targeted by the miR-454 molecule were examined via bioinformatic tools and, it was understood that the relevant miRNA had a repressing feature and accordingly assumed the role of an oncogene. Conclusion: Our study has shown that miR-454, which was previously reported to have high expression levels in cell lines and UMM tumor tissue, is also found at high levels in the serum/plasma of UMM patients. The results suggest that miR-454 can be a diagnostic and prognostic biomarker in uveal malignant melanoma and can be considered as a important therapeutic target.